2020
DOI: 10.3390/polym12051135
|View full text |Cite
|
Sign up to set email alerts
|

Indoxacarb-Loaded Anionic Polyurethane Blend with Sodium Alginate Improves pH Sensitivity and Ecological Security for Potential Application in Agriculture

Abstract: Traditional pesticide formulations show poor utilization and environmental safety due to their low foliage adhesion and large auxiliaries. In this study, a novel and environment-friendly indoxacarb formulation was prepared to improve the pesticide’s utilization rate, target control characteristics and ecological security. Indoxacarb-loaded waterborne polyurethane–sodium alginate (PU/SA) nanoemulsions with film forming properties, alkaline responsive release, high effectiveness against Spodoptera litura, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…12,13 Some efforts have been made to blend PUD (as a major or minor phase) with other polymeric materials, for example, casein-caprolactam, 14 soy protein derivatives, [15][16][17] kefiran, 18 polyethylene oxide, 19 polyacrylate, 20 and sodium alginate. 21 The PUD blending demonstrated improvements in selected properties as well as the sustainability of the final products. Despite the fact that the use of PUD is beneficial to both the environment and the user, there are some drawbacks to this polymer, such as its low thermal resistance, susceptibility to water permeation due to its hydrophilicity, and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 98%
“…12,13 Some efforts have been made to blend PUD (as a major or minor phase) with other polymeric materials, for example, casein-caprolactam, 14 soy protein derivatives, [15][16][17] kefiran, 18 polyethylene oxide, 19 polyacrylate, 20 and sodium alginate. 21 The PUD blending demonstrated improvements in selected properties as well as the sustainability of the final products. Despite the fact that the use of PUD is beneficial to both the environment and the user, there are some drawbacks to this polymer, such as its low thermal resistance, susceptibility to water permeation due to its hydrophilicity, and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 98%
“…are developed as nanocarriers for pesticide delivery and pest control. Huang group used mesoporous silica as a carrier for IDC (loading rate 24%) and studied its insecticidal activity against Plutella xylostella L . Wang and colleagues reported polyurethane-sodium alginate nanopesticide for IDC loading (loading rate: ∼9%) and Spodoptera litura control . Recently, Yang et al developed a carboxylated β-cyclodextrin-anchored hollow mesoporous silica as a carrier for IDC (loading rate: 26.42%) and found that it exhibited a significantly improved antipest performance against S.…”
Section: Introductionmentioning
confidence: 99%
“…19−22 Huang group used mesoporous silica as a carrier for IDC (loading rate 24%) and studied its insecticidal activity against Plutella xylostella L. 23 Wang and colleagues reported polyurethane-sodium alginate nanopesticide for IDC loading (loading rate: ∼9%) and Spodoptera litura control. 24 Recently, Yang et al developed a carboxylated β-cyclodextrin-anchored hollow mesoporous silica as a carrier for IDC (loading rate: 26.42%) and found that it exhibited a significantly improved antipest performance against S. frugiperda. 12 The previous studies have made important development in IDC formulation innovation; however, the pesticide loading rate is low and the preparation process is relatively complex, which means more carriers and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoformulation of indoxacarb was used against the cotton leafworm (Sabry et al, 2021). Indoxacarb formulation was developed to nanoformulation to improve the pesticide's utilization rate, target control characteristics and ecological security (Wang et al, 2020). Spirotetramat also used against wide range of insect pests such as sucking insects in their juvenile, immature stages, including aphids, scale insects and whitefly (Salazar-López et al, 2016).…”
Section: Introductionmentioning
confidence: 99%